INICIATIVAS CIRCULARES PARA O DESENVOLVIMENTO SUSTENTÁVEL: CONTRIBUIÇÃO DAS EMPRESAS B BRASILEIRAS - JULIA MORETTI (2023)
Faced with the current population growth in the Built Environment (BE) and the environmental impact of constructions with the linear economic-industrial business approach, of extraction-consumption-disposal of resources, the present work analyzes the initiatives of the Brazilian companies of the B and how they are contributing to circularity, application of Circular Economy (CE), in BE. For this, the work was structured in the format of two articles. The first article (Chapter 2 of the work) refers to a Systematic Literature Review (SLR), with 57 articles, in order to advance the understanding of how the BE can operationalize the transition to circularity. Through this study, the state of the art of CE in BE, the research directions and what are the circular practices applied in BE through a proposed framework as a result of study. Based on the results, the direction of the study suggests addressing the topics: use of participatory technologies, interdisciplinary studies, focusing on behavioral and social dimensions, and top-down and bottom-up initiatives to promote the advancement of CE in BE. The second article (Chapter 3 of the paper), uses the framework proposed in the first article to conduct a multiple case study with 3 Brazilian B companies. As a result, the three companies report that circular initiatives are part of their organizational strategy, and the motivations, barriers and facilitators of implementing these initiatives vary according to the size, segments and location of the company, however, there is a common indication: the behavioral aspect of people. Companies report economic benefits experienced by adopting sustainability, these benefits encourage not only the perpetuation of the sustainability of their operations, but also of their supplier network, assisting in the transition to circularity.